Professional and higher art-pedagogical education in alleviating social conflicts: experience of China’s ethnic minorities - Liu Xi (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
Studying the experience of the People’s Republic of China in addressing social issues concerning ethnic minorities through their involvement in high art-pedagogical education holds significant relevance for Ukraine. As Ukraine grapples with its own challenges related to the integration and inclusion of ethnic minorities, particularly in the context of cultural preservation and education, the Chinese approach offers valuable insights and potential solutions. The purpose of the article is to present Chinese approaches to solving social problems of national minorities through their access to higher artistic and pedagogical education. In particular, such issues as the preservation of the cultural identity of national minorities, the levelling of social conflicts within the minorities themselves and at the “state-minority” level, access to higher education as a way to resolve social conflicts, and others are considered. Studying China’s experience in addressing social issues concerning ethnic minorities through high art-pedagogical education provides Ukraine with valuable lessons and strategies for promoting cultural preservation, social cohesion, and economic development within its own diverse society. For writing the article, methodological approaches such as Literature Review, Comparative Analysis, Multidisciplinary Approach, and Policy Analysis were used. These methods are typical for scientific research in general education, social education, and comparative studies, allowing the authors to examine the problems from various perspectives. The following results were obtained: The Chinese experience in addressing social conflicts related to ethnic minorities through professional music-pedagogical education can provide valuable insights for Ukraine, which faces similar challenges in its multicultural and multiethnic society. Additionally, it offers practical models for comprehensive social support for ethnic minority representatives.